Acidentes motocicleta-carro: um estudo das representações sociais no trânsito em Goiânia - Ferreira, Cintia Campos (2006)
This work intends to understand traffic accidents involving motorbikes and cars, from a psychosocial model study of traffic. Thus, we have tried to know the representative system which orients and justifies the practices of driving in motorbykers and car drivers. Therefore, in the process of these representations to be studied we have opted to consider the social representation of the traffic context of the chore of driving, of other drivers, of the causes of the traffic accidents, of the culprits for traffic accidents, and to the behavioral excuses about traffic accidents. To know the representation of these groups, we have performed a methodological research based on the Social Representation Theory. Initially, a first study has been carried out, which consisted on a data research, in which data from about two hundred traffic accidents in Goiânia, reported by the Military Police and filed in Detran of Goiás, have been collected. Based on this first study, the second has been carried out, which is composed by two groups, the group of the motorbykers, and the group of the car drivers. To the first group a questionnaire has been employed on one hundred motorbykers and, to the second group, we have employed a questionnaire to one hundred car drivers in the city of Goiânia, targeting to find out the social representation of the group in question. Taken as a whole, the results have indicated that both groups have presented a negative representation of the traffic context, although, in the group of the motorbykers the main element has been the danger, and in the group of car drivers, it has been the element chaos. The representation of the task of driving, in the group of motorbykers has been a negative representation; in other words, these have acknowledged a greater danger in driving a motorcycle. On the other hand, in the group of car drives, has arisen an idealized representation of the task of driving. The representation of the other the car drivers has been a negative representation in the respective groups, both in the motorbykers group and the car driver one, and the main causes have been the inattentiveness, carelessness, and disobedience of the traffic law. In the representation of the responsibles for traffic accidents and in the given excuses there have not been significative differences as the culprits in both groups; both the car driver group and the motorbykers one assigned more blame to the motorbykers, which contradicts the results presented in study one.